Strategi Pemasaran dalam Meningkatkan Minat Nasabah BSI KCP Enrekang (Analisis Manajemen Pemasaran Syariah) - Yunus, Yuli Hardani; Bahri, Andi; Nurfitriani (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2023)
In general, the topography of the area is dominated by hills/mountains. This condition is one of the obstacles faced by BSI KCP Enrekang to attract people to become customers. There are still many areas that have not been touched by the network, which makes it difficult for employees to communicate. This study aims to determine the marketing strategy of BSI KCP Enrekang in attracting customer interest and sharia marketing management analysis of BSI KCP Enrekang's strategy in attracting customer interest. The type of research used in this research is descriptive qualitative research. The approach used is a phenomenological approach. The data used in this study are primary data and secondary data, with data collection techniques carried out using observation, interview and documentation techniques. The results showed that (1) the marketing strategy carried out by BSI KCP Enrekang was to use a marketing strategy using segmentation, targeting, positioning on wadiah products related to market segmentation that BSI KCP Enrekang only adopted a market segmentation approach that focused on demographic, geographic, and socioeconomics to understand the characteristics and needs of customers and customers in the Enrekang area. BSI KCP Enrekang has two target markets to improve their product marketing namely credit and funding target market, market position which includes sharia market share, brand awareness, customer loyalty, image and trust, product innovation, price perception, and range and service, BSI KCP Enrekang can evaluate its position in the Islamic financial market in the region. (2) Sharia marketing management consists of planning function, organizing function, directing and implementation function and monitoring and control function. All of these functions apply the muamalah principle, namely that Islamic banks have avoided the elements of usury which is in line with the principles of ta'awun, unjust elements, gharar elements, maysir elements, while the haram elements can be categorized that when banks have avoided the elements of usury, maysir and gharar, then the haram elements have been gone